2021
DOI: 10.7150/jca.51179
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of KRT19 in Lung Squamous Cancer

Abstract: Backgroud: Keratin 19 (KRT19) is the intermediate filament that constitutes the cytoskeleton and regulates cell-cycle and cell death. Objective: We aimed to assess whether KRT19 was involved in lung cancer development. Methods: The expression of KRT19 in lung cancer was evaluated from mRNA expression on open databse and protein abundance on tumor tissue array. Results: Using open microarray gene expression datasets and differential expression analysis, we found that KRT19 was upregulated in lung cancer compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…It has been demonstrated that the evolutionarily old KRT19 is differentially expressed in several types of cancers. In the present study, KRT19 was found overexpressed in breast, colon, lung, liver and thyroid cancer ( Table 1 ), consistently with previous reports; KRT19 was associated with poor clinical outcomes in cancer patients as well ( Kawai et al, 2015 ; Saha et al, 2019 ; Wang et al, 2019 ; Yuan et al, 2021 ). KRT19 represents one of the factors determining tumor response to chemo/radiotherapy ( Bozionellou et al, 2004 ; Saha et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…It has been demonstrated that the evolutionarily old KRT19 is differentially expressed in several types of cancers. In the present study, KRT19 was found overexpressed in breast, colon, lung, liver and thyroid cancer ( Table 1 ), consistently with previous reports; KRT19 was associated with poor clinical outcomes in cancer patients as well ( Kawai et al, 2015 ; Saha et al, 2019 ; Wang et al, 2019 ; Yuan et al, 2021 ). KRT19 represents one of the factors determining tumor response to chemo/radiotherapy ( Bozionellou et al, 2004 ; Saha et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…8 Upregulation of KRT19 has been reported in various tumor tissues, and KRT19 is associated with tumor proliferation and metastasis, such as lung adenocarcinoma (LUAD), breast cancer (BRCA), hypopharyngeal squamous cell cancer and thyroid cancer (THCA). [9][10][11] However, the expression patterns of KRT19 and its clinical significance in OV remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to MUC1, ELF3, B4GALT1, XBP1 and SLC2A1, 19 other genes (including KRT18, KRT19, KRT8, SFN, CLDN7, FKBP4, CCND1, ELOVL5, RHOD, SLC7A5, MED24, TPBG, AQP3, OVOL2, CISH, STC2, MREG, PMAIP1, and AREG) were screened by us to serve as early diagnostic markers of EC response to estrogen. To date, KRT18 [47], KRT19 [48], KRT8 [49], SFN [50], CLDN7 [51], FKBP4 [52], CCND1 [53], ELOVL5 [54], RHOD [55], SLC7A5 [56], MED24 [57], TPBG [58], AQP3 [59], OVOL2 [60], CISH [61], STC2 [62], PMAIP1 [63], and AREG [64] have been reported to be highly expressed in a variety of cancers and associated with the promotion of cancer cell growth, proliferation, migration and invasion. Only MREG was found to be downregulated in expression in thyroid cancer tissues, and knockdown of MREG promoted cancer cell proliferation and invasion [65].…”
Section: Plos Onementioning
confidence: 99%